The Effect of Economic Growth and Locally Generated Revenue on Financial Independence on Regions in the Province of Bali - Anak Agung Gde Mantra Suarjana; Ketut Arya Bayu Wicaksana; Luh Mei Wahyuni (Politeknik Negeri Bali, 2019)
The purpose of this research are firstly to analyze the effect of economic growth on financial independence on regions in the Province of Bali, secondly to analyze the effect of locally generated revenue toward financial independence on regions in the Province of Bali, thirdly to analyze the effect of economic growth and locally generated revenue on financial independence on regions in the Province of Bali, and fourthly to analyze each regions financial independence in the Province of Bali. Samples collected using purposive sampling method for the last 5 (five) years from each region. The results show that economic growth positively significant affected financial independence of regions in the Province of Bali. The second result show that locally generated revenue has positive and significant effect on financial independence on regions in the Province of Bali. The third findings show that simultaneously economic growth and locally generated revenue have significantly positive effect on financial independence on regions in the Province of Bali. In general, financial independence of each region in the Province of Bali still depend on the central government. It concluded from the low and very low ratio of districts/cities financial independence. Only region of Badung have high ratio on financial independence thus the region of Badung’s locally generated revenue able to fund its own expenditure in their duty to perform regional autonomy.